The future outlook on allergen immunotherapy in children: 2018 and beyond - Stefania Arasi; Giovanni Corsello; Alberto Villani; Giovanni Battista Pajno (BMC, 2018)
Abstract Allergen immunotherapy (AIT) is the only currently available immune-modifying and aetiological treatment for patients suffering from IgE-mediated diseases. In childhood, it represents a suitable therapeutic option to intervene during the early phases of respiratory allergic diseases such as rhino-conjunctivitis and asthma, which is when their progression may be more easily influenced. A growing body of evidence shows that oral immunotherapy represents a promising treatment option in children with persistent IgE- mediated food allergy. The efficacy of AIT is under investigation also in patients with extrinsic atopic dermatitis, currently with controversial results. Furthermore, AIT might be a strategy to prevent the development of a new sensitization or of a (new) allergic disease. However, there are still some methodological criticisms, such as: a) the regimen of administration and the amount of the maintenance dose are both largely variable; b) the protocols of administration are not standardized; c) the description and classification of side effects is variable among studies and needs to be standardized; d) quality of life and evaluation of health economics are overall missing. All these aspects make difficult to compare each study with another. In addition, the content of major allergen(s) remains largely variable among manufacturers and the availability of AIT products differences among countries. The interest and the attention to AIT treatment are currently fervent and increasing. Well-designed studies are awaited in the near future in order to overcome the current gaps in the evidence and furtherly promote implementation strategies.